(untitled) (Jurnal Mu’allim, 2026)
Education of piety is a central objective of Islamic Religious Education that requires guidance strategies not only oriented toward cognitive knowledge but also strengthening spiritual dimensions and the practice of worship. This study examines the implementation of piety education through the Tahajjud Call Program and explores the role of teachers in guiding and developing students’ piety at SMPIT Banten Islamic School. The research aims to describe the implementation of the Tahajjud Call Program while identifying the contribution of Islamic Religious Education teachers in the process of fostering students’ piety. This study employs a qualitative method with a case study design. Data were collected through observation activities, in depth interviews, and document review then analyzed using thematic analysis, data presentation, and conclusion drawing. The findings indicate that the Tahajjud Call Program is implemented systematically and continuously while Islamic Religious Education teachers and homeroom teachers act as spiritual mentors, motivators, role models, and evaluators of program implementation. Personal mentoring through direct communication is proven to improve discipline in worship, strengthen spiritual awareness, and shape students’ religious attitudes. Tahajjud prayer effectively cultivates students piety.